Study of Problem Identification and Solution for Handling the Housing Stimulant Grant Program in the COVID-19 Pandemic: A Case Study in Muncan Village, Bali - Juniartini, Ni Luh Putu; Suwantara, I Ketut; Setiawan, I Nyoman Anom Fajaraditya (Bali Membangun Bali: Jurnal Bappeda Litbang, 2020)
Purpose: The housing rehabilitation program for low-income people is carried out by the Indonesian Ministry of Public Works and Public Housing. Muncan Village is one of the areas that received 2020 house rehabilitation assistance (BSPS) for Karangasem Regency. Research methods: Preventive measures are needed, especially for the Field Facilitator Team as the front guard, so that the BSPS program channelled adequately. The key to smooth distribution, in addition to the precise mechanism, must also follow the government's recommendations and implement health protocols. Findings: Constraints on distribution activities, starting from November 2019 to the initial process in April 2020. Field constraints, social aspects, education, and the community's situation become challenges in these activities. But beginning in 2020, the COVID-19 pandemic made the distribution of aid even more complicated with adjustments to the rules and recommendations of the government in conducting activities. Implications: Additional mission the field team to accelerate the handling of the pandemic, an appeal about anticipating COVID-19 also needs to convey. Strategies related to initiatives provide a masker for beneficiaries to foster protocol awareness and motivation regarding applicable rules.